Post-exercise Cold Water Immersion Does Not Improve Subsequent 4-km Cycling Time-Trial Compared With Passive and Active Recovery in Normothermia - Egaña, Mikel; Allen, Lynn; Gleeson, Kate; Gildea, Norita; Warmington, Stuart (Frontiers in Sports and Active Living, 2021)
Background: We investigated whether a brief cold water immersion between two cycling time trials (TT) improves the performance of the latter compared with passive and active recovery in normothermic conditions ( 20°C). Methods: In Experiment 1 10 active participants (4 women) completed two 4-km TT (Ex1 and Ex2, each preceded by a 12 min moderate-intensity warm-up) separated by a 15 min recovery period consisting of: (a) passive rest (PAS) or (b) 5 min cold water immersion at 8°C (CWI-5). In Experiment 2, 13 different active males completed the same Ex1 and Ex2 bouts separated by a 15 min recovery consisting of: (a) PAS, (b) 10 min cold water immersion at 8°C (CWI-10) or (c) 15 min of moderate-intensity active recovery (ACT). Results: In both experiments, the time to complete the 4-km TT-s was not different (P > 0.05, ES = 0.1) among the trials neither in Ex1 (Experiment 1: PAS: 414 ± 39 s; CWI-5: 410 ± 39 s; Experiment 2: PAS: 402 ± 41 s; CWI-10: 404 ± 43 s; ACT: 407 ± 41 s) nor Ex2 (Experiment 1: PAS: 432 ± 43 s; CWI-5: 428 ± 47 s; Experiment 2: PAS: 418 ± 52 s; CWI-10: 416 ± 57 s; ACT: 421 ± 50 s). In addition, in all conditions, the time to complete the time trials was longer (P < 0.05, ES = 0.4) in Ex2 than Ex1. Core temperature was lower (P < 0.05) during the majority of Ex2 after CW-5 compared with passive rest (Experiment 1) and after CWI-10 compared with PAS and ACT (Experiment 2). Perceived exertion was also lower (P < 0.05) at mid-point of Ex2 after CWI-5 compared with PAS (Experiment 1) as well as overall lower during the CWI-10 compared with PAS and ACT conditions (Experiment 2). Conclusion: A post-exercise 5–10 min cold water immersion does not influence subsequent 4-km TT performance in normothermia, despite evoking reductions in thermal strain.